Competition and Nonprofit’s Strategic Responses: Evidence from Fundraising in Donative Markets - Gayle, Philip G.; Harrison, Teresa D. (The Review of Economics and Statistics, 2026)
Nonprofit organizations rely on donations from large competitive marketplaces to provide key social service goods. Most research focuses on competition in output markets without considering philanthropic markets where nonprofits make decisions about how much effort to put into fundraising. We develop and estimate a model that highlights the strategic nature of fundraising, showing that rival NP’s fundraising responses can be strategic complements or substitutes. We find evidence of strategic substitutes. NPs demonstrate nontrivial strategic responses to rival’s fundraising and, in totality, the across sector impacts are important to consider. Counterfactual exercises show that reducing competition decreases equilibrium fundraising levels.